Eksplorasi Strategi Pengumpulan Data Dalam Penelitian Kualitatif Dan Kuantitatif; Studi Perbandingan Metode Tesis Di Kalangan Akademisi - Lestari, Nopita; Aprisa , Melda Tri; Dewi, Desy Eka Citra (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This study aims to explore data collection strategies in qualitative and quantitative research, with a focus on comparing methods used by academics. In the context of academic research, data collection is a crucial aspect that determines the validity and reliability of findings. This study uses a descriptive-analytical approach by analyzing various academic theses published in 2023. The results show that the qualitative method tends to use in-depth interviews and participatory observation, while the quantitative method predominantly uses surveys and experiments. Furthermore, significant variation was found in the selection of methods, influenced by the field of study and research objectives. This study provides practical insights for researchers in selecting data collection methods that align with their research needs